Water Sources. Water Heritage of the Historic Center of Cusco - Salas Velásquez, Victor (2023)
The objective of this research is to determine the types of water sources and their use in public spaces in the historic center of Cusco through a qualitative historiographical investigation. The results show that in the Inca society they were used ceremonially in the configuration of the Apu Llaqta (sacred settlement), changing the paradigm in the colonial period as it was the main water supply in public and private spaces under a Renaissance and Baroque conception, reaching at its height in the republican period until its disuse due to the negative impact of the modernizing paradigm, continuing like this during the 20th century. As a result of the field study, it was found that water sources are considered as ornamental architectural elements of urban equipment; in its configurations, both the matter and the manifestation of the water resource are a unit, but those of the viceroyalty and modern style do not have water, only those of the Inca and contemporary style preserve the water that, after having an ornamental use, ends up in the drainage system. sewage or drainage because the current local management does not recognize the water heritage.